The evaluation of the correct use and ease‐of use of the ELLIPTA DPI in children with asthma. Issue 1 (19th November 2020) - Halverson, Philip; Liem, Joel; Heyes, Logan; Preece, Andy; Bareille, Philippe; Rees, Jamie; Jain, Renu; Stanford, Richard H.; Lenney, Warren; Collison, Kathryn; Sharma, Raj
Abstract: Rationale: Asthma studies show many children use inhalers incorrectly even after instruction. For two age groups of children with asthma, we determined the proportions who used the once‐daily ELLIPTA dry‐powder inhaler (DPI) correctly, and who found it easy to use. Methods: This was a multicenter, single‐arm, stratified, open‐label, placebo study (NCT03478657). Children aged 5–7 and 8–11 years were trained in, and required to demonstrate, correct placebo ELLIPTA DPI use at their first clinic visit. The inhaler was used at home once daily for 28 ± 2 days. On returning to the clinic, children were randomized to an age‐appropriate, ease‐of‐use questionnaire that had been developed and validated previously, and which rated the inhaler as "easy" or "hard" to use. Following questionnaire completion, children were then asked to demonstrate correct inhaler use. Correct use and ease‐of use were assessed in each age group (co‐primary endpoints) and overall (secondary endpoints). Results: Of 222 enrolled children, 221 completed the study. Among children aged 5–7 years, 92% ( n = 81/88) demonstrated correct ELLIPTA use on their first attempt, compared with 93% ( n = 124/133) aged 8–11 years. Of these children, 98% (5–7 years: n = 79/81; 8–11 years: n = 121/124) rated the inhaler easy to use. Overall, 93% ( n = 205/221) demonstrated correct inhaler use on their first attempt, and 98% ( n = 200/205) rated it easy to use. Conclusion: ELLIPTA DPI was used correctly and easily by most children on their first attempt without additional training.